Cervical Myolipoma with Pregnancy: Report of a Case and Brief Review of Literature - Manila, Kaushal; Laxmi, Maru; Ranjana, Patidar (Nepal Journal of Obstetrics and Gynaecology, 2011)
DOI: http://dx.doi.org/10.3126/njog.v4i2.5049 NJOG 2010 Jan-Feb; 4(2): 54-55